Monitoring interaction between universities and educational institutions when working with gifted youth - S. A. Piyavsky; Z. F. Kamaldinova; V. V. Kozlov; YU. I. Nudelman; R. B. Shatalov; G. P. Savelieva; E. A. Fedorova (Moscow Polytechnic University, 2022)
The value of the creative part of the human potential will determine the place occupied byRussia on the world stage. The sphere of science and technology is of particular importance. This article shows how using modern intelligent tools for collecting, processing and analyzing information it is possible to ensure centrally coordinated by a roll-call monitoring and supportof talented young people. This system should accumulate the resources and capabilities of the state, employers and society in general.